DAMP-driven trained immunity: metabolic and epigenetic reprogramming in critical illness and chronic inflammation - Kim, Han G.; Rincon, Jaimar C.; Efron, Philip A.; Maile, Robert (Frontiers in Immunology, 2025)
Innate immune memory, traditionally underappreciated in contrast to adaptive immunity, is now recognized as a critical component of host defense, particularly in the context of sepsis and sterile inflammatory injury. Recent advances have identified a central role for metabolic and epigenetic reprogramming in driving trained immunity (TRIM), where monocytes, macrophages, and other innate cells develop enhanced or tolerized responses to secondary stimuli. This review synthesizes current knowledge of how damage-associated molecular patterns (DAMPs), including oxidized LDL, HMGB1, heme, urate crystals, and mitochondrial DNA, serve as potent inducers of immunometabolic rewiring, often through the mTOR/HIF-1α axis or alternative pathways such as SYK signaling. We highlight distinct epigenetic mechanisms, such as enhancer priming via H3K4me1/H3K27ac, and metabolic shifts like the Warburg effect, succinate accumulation, and fatty acid synthesis, that define the trained or tolerized states. Particular attention is given to the relevance of these mechanisms in the pathophysiology of sepsis, burns, trauma, and other critical illnesses where persistent DAMP exposure may sustain maladaptive inflammation or immunosuppression. We review data linking central (stem cell-level) and peripheral reprogramming to long-term immune dysfunction in various inflammatory disease models, and explore how DAMPs intersect with PAMPs to shape the immune trajectory. Finally, we identify pressing gaps in the field, including the need for standardized TRIM models, validated biomarkers of innate memory, and mechanistic clarity on mitochondrial DAMPs in immune tolerance. These insights provide a foundation for future therapeutic strategies aimed at modulating trained immunity to improve outcomes in critically ill patients.